The use of cheese whey powder in the cultivation of protein-rich filamentous fungal biomass for sustainable food production - Kaya, Burcu; Wijayarathna, E. R. Kanishka B.; Yüceer, Yonca Karagül; Agnihotri, Swarnima; Taherzadeh, Mohammad J.; Sar, Taner (Frontiers in Sustainable Food Systems, 2024)
Cheese whey is an industrial by-product that is generated in excess during the cheese production process in the dairy industry. Despite the potential utility of whey, it continues to pose environmental threats in the industry. This study comprehensively evaluates the utilization of two fermentation techniques (solid-state fermentation and submerged fermentation) for producing fungal biomass from cheese whey powder, employing Aspergillus oryzae, Rhizopus oryzae, and Neurospora intermedia for sustainable food production. It has been observed that submerged fermentation is more effective in increasing the protein content of whey powder compared to solid-state fermentation. The highest biomass yield was achieved with A. oryzae (5.29 g/L, 0.176 g biomass/g substrate), followed by N. intermedia (3.63 g/L, 0.121 g biomass/g substrate), and R. oryzae (1.9 g/L, 0.063 g biomass/g substrate). In the bubble column reactor, the protein content of the substrate (78.65 g/kg) increased by 165.54 and 176.69% with A. oryzae (208.85 g/kg) and N. intermedia (217.62 g/kg), respectively. This study has demonstrated that whey powder can be converted into protein-rich biomass through fungal bioconversion. The obtained biomass has the potential to be developed as an alternative food and feed source, contributing to waste management and sustainable food production.